Reusable Non-Interactive Secure Computation - Chase, Melissa; Dodis, Yevgeniy; Ishai, Yuval; Kraschewski, Daniel; Liu, Tianren; Ostrovsky, Rafail; Vaikuntanathan, Vinod (Crypto 2019, 2019)
We consider the problem of Non-Interactive Two-Party Secure Computation (NISC), where Rachel wishes to publish an encryption of her input x, in such a way that any other party, who holds an input y, can send her a single message which conveys to her the value f(x, y), and nothing more. We demand security against malicious parties. While such protocols are easy to construct using garbled circuits and general non-interactive zero-knowledge proofs, this approach inherently makes a non-black-box use of the underlying cryptographic primitives and is infeasible in practice.